Business confidence of the province of Chimborazo, period 2021 - González Bautista, María; Tamayo Ruiz , Alexa; Alvarez Basantes, Karina; Zurita Moreano, Eduardo (mktDESCUBRE, 2023)
The Business Confidence Index (ICE) measures the perception and expectations of the business sector regarding its economic activity. For its calculation, the most representative companies of the province of Chimborazo of the economic sectors (commerce, construction, industry and services) are analyzed. The methodology used is that established by the Central Bank of Ecuador, with primary information collected from 145 companies, through monthly business opinion surveys (July-August 2021). The results show that the global ICE in the province reaches 27.19 points in the month of July 2021, which shows that the confidence of local companies in the economic environment is favorable. Companies in the service and industrial sectors present a positive ICE with 67.36 and 67.61 points respectively, so there is evidence of a certain economic reactivation where consumers have increased the demand for goods and services. On the other hand, the commerce and construction sectors have an ICE score of -40.19 and -54.10, respectively, due to the limited incentives that companies in these sectors have received and the spending austerity policies implemented by the government.